A Comprehensive Analysis of Cultural Migration and its Crucial Study with Regard to Feminism (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Cross-cultural encounters between feminism and migration are explored in this study, Feminism and Migration: Cross-Cultural Engagement is a valuable resource. Some of the most well-known and emerging scholars in this field provide in-depth analyses of how social, cultural, political, and economic forces influence the new perspectives that women on the move develop through a variety of topics, such as theorizing feminism in migration and the contesting identities and agency that these topics entail. It emphasizes the significance of feminism's diverse meanings and interpretations. And the main study in which discussed A Comparison from the Feministic Point of View, A Comparison from the Cultural Point of View, The Cultural Conflict, and The Isolation of women.